ANALISIS TINGKAT KEPUASAN SISWA PADA KELAS KHUSUS ATAS KUALITAS PELAYANAN JASA PENDIDIKAN DI SMK LABOR BINAAN FKIP UNRI PEKANBARU - Narsih, Meli; Haryana, Gani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack: This research purpose is to know how the level of the student satisfaction in special classes on the quality of educational services was SMK Labor Binaan FKIP UNRI Pekanbaru with fourty one (41) sample can obtained with Taro Yamane Formula and the method to take the sampling use area sampling method (cluster sampling). The analysis data technique using on the research is Importance and Performance Analysis (IPA) that compare with the importance or performance level. The result can be showed that importance score is 185.93 while that performance score is 151.75. This matter that point the performace score of student are low so far of student wants. It means that students have less satisfied on services at the school while the level of suitability scored are good with score is 81.80%. Because that the school can repairing that performance in there. And satisfied of student can realize to all indicator at shcool.Keywords : Services Quality and Costumers Satisfaction